Potential, Challenges and Opportunities of Balinese Language in The Middle of Globalization Effects - Ni Luh Sukanadi; Ida Ayu Made Wedasuwari; Ni Wayan Eminda Sari; I G. A. Putu Tuti Indrawati (Denpasar Institute, 2022)
Language is a component of nationalism, as stated in the youth oath “trilogy” which has been interpreted, among others, by